Spectrophotometric study of inclusion complexation of aliphatic alcohols by β-cyclodextrins with azobenzene tether - Liu, Yu (2011)
Two novel β-cyclodextrin (β -CD) derivatives possessing azobenzene functional groups as a spectral probe, i.e., mono{6-O-[4-(phenylazo)phenyl]}- β -cyclodextrin (1) and mono{6-O-[4-((4-nitrophenyl)azo)phenyl]}- β-cyclodextrin (2), were synthesized in high yields, and their complexation behaviors with aliphatic alcohols were evaluated by using UV-vis, circular dichroism, and 1H NMR spectroscopy. The induced circular dichroism (ICD) and 2D NMR spectroscopy investigations revealed that azobenzene groups attached to the β-CD rim can be deeply embedded to the β-CD cavity to form the intramolecular inclusion complexes in 10% DMSO aqueous solution. Increasing the ratio of DMSO in solution results in the gradual exclusion of the azobenzene sidearm from the β-CD cavity. Upon complexation with guest adamantanols, modified β-CD 1 or 2 displays two different binding models, that is, the competitive inclusion model for 2-adamantanol and the co-inclusion model for 1-damantanol. These two different models reasonably explain the different binding behaviors and molecular selectivities of host β-CDs toward guests. Therefore, besides acting as a spectral probe, azobenzene modified β-CDs can also effectively recognize the size/shape of guest molecules, giving good molecular selectivity up to 91 for 2-adamantanol/(+)-borneol pair by 1 and the modeate enantioselectivity (K-/K+ = 2.1) for (-)-/(+)-borneol pair by 2.